ACTFL-Based Computerised Adaptive Testing for Quality Management in Arabic Instruction at an Islamic University - Ihwan Mahmudi; Moh Ismail; Taufik Rizki Sista; Ahmad Saifulloh; Syarifah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
This research examines the implementation of Computerized Adaptive Testing based on ACTFL standards at Universitas Darussalam Gontor (UNIDA). In the midst of the increasing adoption of global language assessment standards. This research employs a qualitative approach, utilizing thematic analysis. Data were obtained through in-depth interviews with university leaders, quality assurance units, lecturers, system developers, and students. The results show that CAT-ACTFL not only functions as an instrument for measuring language proficiency, but also becomes an important part of academic governance, curriculum management, and the strengthening of data-based quality assurance systems. Its implementation reflects a strategic alignment between global assessment standards and UNIDA's institutional vision framework, positioning Arabic as a pillar of academic policy and learning planning. This study introduces a new model of Pesantren-Aligned Language Assessment Governance as a key novelty, demonstrating that the global CAT-ACTFL standards can integrate harmoniously with the local values of pesantren. This research makes a significant contribution to educational management by transforming static quality assurance into a dynamic, data-driven system for differentiating Arabic language instruction in higher education. Nevertheless, this research also indicates the importance of further evaluation of the quality of the ACTFL instruments used. Therefore, further research is recommended to conduct validity and reliability testing and to analyze the item characteristics of the CAT-ACTFL instruments using psychometric approaches, such as Item Response Theory (IRT) and the Rasch Model, to ensure more precise and scientific measurement of language proficiency.